2012
DOI: 10.4040/jkan.2012.42.5.719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hospital Nurse Staffing on in-hospital Mortality, Pneumonia, Sepsis, and Urinary Tract Infection in Surgical Patients

Abstract: Purpose: This study was done to examine relationships between nurse staffing level and postsurgical patient outcomes using inpatient database from the National Health Insurance. Methods: Records of 111,491 patients who received one of 12 types of surgery between January and December, 2009 were identified and analyzed in this study. Nurse staffing level was measured using adjusted nurse staffing grades from 0 to 7. Patient outcomes were defined as in-hospital mortality, or pneumonia, sepsis, or urinary tract in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
7
26
1
Order By: Relevance
“…Severity may need to be adjusted using paediatric pressure ulcer risk‐assessment tools such as the Braden Q Scale and Glamorgan Scale, which include more sensitive risk factors such as incontinence, mobility, nutritional status, tissue oxygenation, and perfusion (Baharestani & Ratliff, ). Further, in previous studies in the adult population, nurse staffing levels and lower rates of failure to rescue have been associated (Kim, Cho, June, Shin, & Kim, ), which differs from the results of this study. Failure to rescue may need to be adjusted using paediatric mortality risk assessment tools, such as the Pediatric Risk of Mortality III (PRISM III) score, and the Sequential Organ Failure Assessment (SOFA) score (Kim et al., ; ; Pollack et al., ; ).…”
Section: Discussioncontrasting
confidence: 99%
“…Severity may need to be adjusted using paediatric pressure ulcer risk‐assessment tools such as the Braden Q Scale and Glamorgan Scale, which include more sensitive risk factors such as incontinence, mobility, nutritional status, tissue oxygenation, and perfusion (Baharestani & Ratliff, ). Further, in previous studies in the adult population, nurse staffing levels and lower rates of failure to rescue have been associated (Kim, Cho, June, Shin, & Kim, ), which differs from the results of this study. Failure to rescue may need to be adjusted using paediatric mortality risk assessment tools, such as the Pediatric Risk of Mortality III (PRISM III) score, and the Sequential Organ Failure Assessment (SOFA) score (Kim et al., ; ; Pollack et al., ; ).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to that of LOS and medical expenses, an inverse relationship between nurse staffing and nurse sensitive outcomes (e.g. urinary tract infections, pneumonia, and wound infections) has been amply demonstrated (Cho et al ., ; Lankshear et al ., ; Kane et al ., ; Cho & Yun, ; Kim et al ., ). The occurrence of these adverse events could be associated with a significantly prolonged LOS and could subsequently increase healthcare expenses.…”
Section: Discussionmentioning
confidence: 97%
“…Research evidence concerning the relationship between nurse staffing and patient outcomes has increased. Most studies report an association of increased registered nurse (RN) staffing levels with lower rates of hospital mortality and adverse patient events in Korea, as well as in other countries (Lankshear et al ., ; Kane et al ., ; Cho & Yun, ; Kim et al ., ). However, a systematic review found a mixed impact of nurse staffing on hospital costs or LOS (Thungjaroenkul et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The 12 types of surgery analyzed in this study were determined using Korean Diagnosis-Related Group (KDRG) categories with relatively high death rates according to previous studies (craniotomy, cardiovascular surgery, digestive system surgery, and hepatobiliary system surgery). Their KDRG categories were as follows: major craniotomy except for trauma (B011-B019), other craniotomy except for trauma (B021-B022), craniotomy for trauma (B030), cardiac valve procedure with cardiac catheter (F021-F023), cardiac valve procedure without cardiac catheter (F031-F033), coronary bypass with/without cardiac catheter (F041-F044), major reconstructive vascular procedure (F061-F064), amputation for circulatory system disorders (F120), esophageal procedure (G011-G013), major small and large bowel procedure (G031-G033), stomach and duodenal procedure (G041-G046), and pancreas, liver and shunt procedure (H011-H016) [1][2][3]17]. The exclusion criteria encompassed patients who had been transferred to other hospitals during their hospital stay after surgery, inpatients in special treatment rooms (aseptic rooms, isolated rooms, rooms with lead shielding, etc.…”
Section: Setting and Participantsmentioning
confidence: 99%